The Fourier approximation for orbital elements for the members of very young asteroid families. (August 2021) - Rosaev, A.; Plávalová, E.
Abstract: We applied the Fourier approximation in studying the dynamics of very young asteroid families (younger than 1.6 Myr). As the output, we obtained a new system of approximated orbital elements, which is comparable to classical elements. We have found only one significant discrepancy in the perihelion longitude rate of the Rampo family's main member. Moreover, we extended our system of approximated elements by including amplitudes and frequencies of the periodic variations of angular elements. Highlights: Fourier approximation was applied in studying the dynamics of VYFs. A system of proper elements, adapted to studying Very Young asteroid Families (VYFs). The values of main harmonics in angular element perturbations are calculated and explained. VYFs are dynamically subdivided into resonance and regular.